Bioacoustic-enabled patterning of human iPSC-derived cardiomyocytes into 3D cardiac tissue. (July 2017) - Serpooshan, Vahid; Chen, Pu; Wu, Haodi; Lee, Soah; Sharma, Arun; Hu, Daniel A.; Venkatraman, Sneha; Ganesan, Adarsh Venkataraman; Usta, Osman Berk; Yarmush, Martin; Yang, Fan; Wu, Joseph C.; et al.
Abstract: The creation of physiologically-relevant human cardiac tissue with defined cell structure and function is essential for a wide variety of therapeutic, diagnostic, and drug screening applications. Here we report a new scalable method using Faraday waves to enable rapid aggregation of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) into predefined 3D constructs. At packing densities that approximate native myocardium (10 8 -10 9 cells/ml), these hiPSC-CM-derived 3D tissues demonstrate significantly improved cell viability, metabolic activity, and intercellular connection when compared to constructs with random cell distribution. Moreover, the patterned hiPSC-CMs within the constructs exhibit significantly greater levels of contractile stress, beat frequency, and contraction-relaxation rates, suggesting their improved maturation. Our results demonstrate a novel application of Faraday waves to create stem cell-derived 3D cardiac tissue that resembles the cellular architecture of a native heart tissue for diverse basic research and clinical applications. Graphical abstract: Schematic summary of the bioengineering approach to create 3D cardiac tissue analogues.A: Culture and cardiomyocyte (CM) differentiation of human induced pluripotent stem cells (hiPSCs).B: Faraday wave patterning of hiPSC-CMs in fibrin prepolymer, generating highly-packed 3D cell construct.C: Cell encapsulation in 3D fibrin hydrogel and culture in vitro, leading to the formation of inter-connected cell bands that exhibit physiologically-relevant CM density and contractile function.